2011
DOI: 10.1021/cg200883b
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures and Photophysical Properties of 9-Anthracene Carboxylic Acid Derivatives for Photomechanical Applications

Abstract: Molecular crystals composed of 9-anthracene carboxylic acid (9AC) can undergo reversible light-induced mechanical motions driven by a [4 + 4] photodimerization reaction. This paper explores the structure, photophysics, and photomechanical response of a family of anthracene carboxylic acid derivatives, with the goal of finding materials that have comparable or improved photomechanical properties. We find that methyl or phenyl substitution at the 10-position leads to a complete loss of photoreactivity due to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 34 publications
1
87
0
1
Order By: Relevance
“…[11][12][13][14][15][16][17][18] Macroscale molecular crystals rarely present ideal deformation properties and it is still a challenge to use molecular crystals in macroscale actuators. Nevertheless, molecular crystal actuators are fragile and are highly restricted in performance by the crystal size and shape.…”
Section: Tian Lan and Wei Chen*mentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18] Macroscale molecular crystals rarely present ideal deformation properties and it is still a challenge to use molecular crystals in macroscale actuators. Nevertheless, molecular crystal actuators are fragile and are highly restricted in performance by the crystal size and shape.…”
Section: Tian Lan and Wei Chen*mentioning
confidence: 99%
“…Various types of photomechanical behaviors such as contraction [8,10], expansion [11], OPEN ACCESS bending [8,[11][12][13][14][15][16][17], separation [18], twisting [19], and rolling [12] have been reported so far. Although photochromic compounds such as diarylethenes [8,19], furylfulgide [20], azobenzene [21,22], anthracene carboxylates [23][24][25][26][27][28], salicylideneaniline [29], 4-chlorocinnamic acid [30], 1,2-bis(4-pyridyl)ethylene salt [31], benzylidenedimethylimidazolinone [32], and others [33] exhibit photochemical reactions in the crystalline phase, their photomechanical motions in the crystal are almost bending. It is essential for the development of the research field of photomechanical crystals to investigate the crystal bending behavior in detail.…”
Section: Introductionmentioning
confidence: 99%
“…T he growing recognition that rapid energy transfer between molecules of tightly packed, ordered crystals of molecular solids could be utilized as a physical platform for actuation from the nanoscale to the macroscale has recently boosted research on mechanically responsive organic-based molecular crystals [1][2][3][4][5][6][7][8][9][10][11][12] . This rapidly expanding research field has revealed an increasing number of examples of oftentimes serendipitous observations of nano-, milli-and macro-sized single crystals that hop [12][13][14] , bend [15][16][17][18][19][20] , curl 21,22 , twist [23][24][25] or swim 26 when exposed to light, heat or external pressure.…”
mentioning
confidence: 99%